Pola Komunikasi Interpersonal dalam Hubungan Orang Tua dan Anak Berkebutuhan Khusus (ABK) - Wicaksana, Fajar Putra; Rosadi, Raesita Rakhmawati (PROPAGANDA, 2024)
Children with special needs are often labeled as special children because in general caring for and raising children with special needs (ABK) requires different parenting and education patterns from ordinary children. This research aims to understand communication patterns between parents and children with special needs, especially children with autism. The research method used is qualitative with descriptive data analysis. Observations were carried out on a family in West Jakarta consisting of a single mother and three children, where the eldest child, 7 years old, was diagnosed with autism. This research also involved in-depth interviews with mothers as the main source. The research results show that effective communication approaches for children with special needs vary according to the child's needs and responses. Parents adopt a variety of methods, from a heart-to-heart approach to a firm but personal approach, to help their children develop better social skills and behavior. A supportive and positive environment plays an important role in the development of children with special needs, providing positive affirmations and messages that improve the child's response and mental development. On the other hand, a negative environment can have a negative impact on a child's development. It is hoped that this research can become a reference for educators, therapists and other professionals in developing more effective intervention methods for autistic children.